Higher Education in Light of the Cross - Ashmon, Scott A. (Dialog, 2015)
What is the summum bonum of a university education? The much lauded liberal approach of Aristotle, Newman, and Roche proposes that education is for contemplating the truthan intrinsic, joyous end in itself. This approach offers the benefits of pursuing truth, virtues, and intellectual habits, but it also carries with it the temptations of idealatry and homo incurvatus in se. Christian universities can reform this approach to education, though, with Luther's theology of the cross, reorienting it through the crucified Christ toward the highest ends of life revealed in God's word: faith in God and love for the neighbor.